2012
DOI: 10.1587/elex.9.1083
|View full text |Cite
|
Sign up to set email alerts
|

A harmonic suppression and size-reduced rat-race hybrid coupler using dual coupled-lines

Abstract: Abstract:A newly proposed coupled-line low-pass filter structure is firstly integrated into rat-race coupler design in this paper for size reduction and harmonic suppression. This low-pass filter is composed of dual parallel coupled-lines with one open stub at the end. By properly substituting this low-pass filter unit cell (LUC) for each one of the six λ/4 sections in the conventional rat-race coupler, significant size reduction and harmonic suppression can be achieved while the property of this proposed coup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In spite of the many advantages and applications, the large circuit area requirement especially at lower microwave frequencies and higher-order harmonics are the inherent drawbacks of the conventional RRC. Different approaches such as stub-loaded transmission lines [2, 3], low-pass filter unit cell (LUC) [4], and meandering technique [5, 6] have been reported to reduce the size and improve the harmonic suppression capability of the RRCs. Next, to meet the wideband requirement of modern communication systems, microwave devices with wide bandwidth and compact size are in demand.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the many advantages and applications, the large circuit area requirement especially at lower microwave frequencies and higher-order harmonics are the inherent drawbacks of the conventional RRC. Different approaches such as stub-loaded transmission lines [2, 3], low-pass filter unit cell (LUC) [4], and meandering technique [5, 6] have been reported to reduce the size and improve the harmonic suppression capability of the RRCs. Next, to meet the wideband requirement of modern communication systems, microwave devices with wide bandwidth and compact size are in demand.…”
Section: Introductionmentioning
confidence: 99%
“…These couplers, however, occupy a large space in an MIC or MMIC. The authors have also reported broadband/tri-band branch-line couplers utilizing open-circuited series stubs [7,8] [24] have also been reported. In these papers, hybrid rings in which a 270-degree line is replaced with a −90-degree CRLH-TL are proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Microstrip LPF is frequently used because of its easy fabrication and good skirt performance. However, it can handle only low power, only up to several hundreds of input power [1,2,3]. A tubular LPF using coaxial line capacitors of rectangular shape and air-core inductors was presented [4,5].…”
Section: Introductionmentioning
confidence: 99%